Re‐engineering the Immune Response to Metastatic Cancer: Antibody‐Recruiting Small Molecules Targeting the Urokinase Receptor. Issue 11 (16th February 2016) - Rullo, Anthony F.; Fitzgerald, Kelly J.; Muthusamy, Viswanathan; Liu, Min; Yuan, Cai; Huang, Mingdong; Kim, Minsup; Cho, Art E.; Spiegel, David A.
Abstract: Developing selective strategies to treat metastatic cancers remains a significant challenge. Herein, we report the first antibody‐recruiting small molecule (ARM) that is capable of recognizing the urokinase‐type plasminogen activator receptor (uPAR), a uniquely overexpressed cancer cell‐surface marker, and facilitating the immune‐mediated destruction of cancer cells. A co‐crystal structure of the ARM‐U2/uPAR complex was obtained, representing the first crystal structure of uPAR complexed with a non‐peptide ligand. Finally, we demonstrated that ARM‐U2 substantially suppresses tumor growth in vivo with no evidence of weight loss, unlike the standard‐of‐care agent doxorubicin. This work underscores the promise of antibody‐recruiting molecules as immunotherapeutics for treating cancer. Abstract : Marked for death : A small‐molecule immunotherapeutic strategy involves the selective tagging of cancer cells for immune‐cell recognition and targeted destruction. This approach holds tremendous promise in guiding the development of selective treatments against highly aggressive metastatic cancers with potentially few side effects.